2018
DOI: 10.1186/s12932-018-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of hydrous manganese oxide on the retention and lability of dissolved organic matter

Abstract: Minerals constitute a primary ecosystem control on organic C decomposition in soils, and therefore on greenhouse gas fluxes to the atmosphere. Secondary minerals, in particular, Fe and Al (oxyhydr)oxides—collectively referred to as “oxides” hereafter—are prominent protectors of organic C against microbial decomposition through sorption and complexation reactions. However, the impacts of Mn oxides on organic C retention and lability in soils are poorly understood. Here we show that hydrous Mn oxide (HMO), a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 102 publications
(164 reference statements)
0
47
2
Order By: Relevance
“…The adsorption, fractionation, and oxidative transformation upon reaction of dissolved organic matter with minerals are dependent on mineral surface chemistry, including the composition and abundance of terminal bonds 123,147 . Despite typically lower adsorptive capacities, Mn oxides are stronger oxidants than Fe oxides, in large part owing to differences in redox potential 123,148,149 . Indeed, Mn oxides are considered the strongest naturally occurring oxidants, and thus considerable attention has been placed in investigating the role of Mn oxides in organic carbon transformations 143 .…”
Section: [H1] Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption, fractionation, and oxidative transformation upon reaction of dissolved organic matter with minerals are dependent on mineral surface chemistry, including the composition and abundance of terminal bonds 123,147 . Despite typically lower adsorptive capacities, Mn oxides are stronger oxidants than Fe oxides, in large part owing to differences in redox potential 123,148,149 . Indeed, Mn oxides are considered the strongest naturally occurring oxidants, and thus considerable attention has been placed in investigating the role of Mn oxides in organic carbon transformations 143 .…”
Section: [H1] Catalysismentioning
confidence: 99%
“…Nevertheless, correlations between oxidized Mn and oxidized OM point to a causal link between Mn oxidation and carbon transformations 113,149,151 . In fact, the intimate and diverse association of OM with Mn oxides 149,152 leads to a continuum of reactions, including mineralization and polymerization within layers coating the oxide surface 129 157,161 .…”
Section: [H1] Catalysismentioning
confidence: 99%
“…In the case of Fe, for example, Fe-coprecipitates may form in environments subjected to redox oscillations (Coward et al, 2018). But in most soils, nanoCLICs likely incorporate a large number of major cations other than Fe and Al, such as Si, Mn (Stuckey et al, 2018), or to a lesser extent more soluble species such as Ca (Rasmussen et al, 2018), Mg or even monovalent species as K (Grand and Lavkulich, 2015), depending on the physical-chemical conditions (concentrations, pH, redox, etc.). Recent studies showed in particular the important role played by Ca in ternary complexation mechanisms (Rowley et al, 2018;Sowers et al, 2018) and its importance in stabilizing OM in rather arid soils and in soils with a pH above 7 (Kramer and Chadwick, 2018;Rasmussen et al, 2018).…”
Section: Implications For Soilsmentioning
confidence: 99%
“…Water-soluble organic substances (WOS) are able to form stable compounds of complex nature with aluminum, manganese, and iron ions [1][2][3][4][5]. There is a close correlation between soil acidity and the mobilization of aluminum and iron from the crystal lattice of minerals [6][7].…”
Section: Introductionmentioning
confidence: 99%